Generative AI and the scientific landscape: a bibliometric exploration of its global impact - Cossio Franco, Edgar Gonzalo; Sossa Azuela, Juan Humberto; Larios Rosillo, Víctor Manuel; Maciel Arellano, Rocio; Arreola Marín, María Esmeralda; Chávez Marcial, Mariela; Alcántar Alcántar, José Iraic; Viñas Álvarez, Samuel Efrén; Briseño Martínez, Ramón Alejandro; Del Valle Soto, Carolina (International Journal of Combinatorial Optimization Problems and Informatics, 2026)
The present comparative bibliometric study (2020-2025) of the Scopus and WoS databases on Generative Artificial Intelligence (GenAI) reveals accelerated growth, concentrating more than 95% of the production and reaching its peak impact in 2025. Thematically, the intersection of communication and technology/education dominates. Geographically, the United States leads production, but Asia-Pacific institutions (Hong Kong) are key. The field of GenAI is a massive trend driven by concentrated collaboration between North America and Asia. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2026.v17i2.1281 Dimensions. Open Alex.